The Rebels' Credibility Dilemma. (4th August 2016) - Thomas, Jakana L.; Reed, William; Wolford, Scott
Abstract: This article examines why rebel groups make large demands of governments that are inconsistent with their fighting capacity, especially when such demands are almost always rejected. We show that making large demands, even if ultimately rejected by the government, makes sense for rebels who face a credibility dilemma. Such a dilemma is most likely to arise when militarily weak rebel groups face governments of uncertain strength and can commit to fight credibly only when they believe the government is also weak. This results in a counterintuitive set of strategic incentives for weak rebels, who choose their demands to ensure that they are rejected even when the government is weak. Thus, to make their threat to fight credible, weak rebels make large demands that, when rejected, result in inefficient fighting. Since most civil wars are characterized by weak rebels bargaining with much stronger governments, it is important to understand how this particular feature of civil war shapes intrawar negotiations between the rebels and the government. We develop a model of bargaining between a government and rebel group and evaluate its implications using historical data on civil conflict in Africa from 1989 to 2010. The results suggest that the tendency for the government to be significantly stronger than rebels induces rebel groups to make unrealistically large demands.